Growth impacts of the exchange rate and technology - Alejandro Márquez-Velázquez (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
The aim of this paper is to assess whether the impacts of real exchange rate undervaluation and domestic technological capabilities on growth are stable across development levels. On the one hand, a real exchange undervaluation measure is constructed based on the purchasing-power-parity theory corrected by the Balassa-Samuelson effect. On the other hand, the index of technological specialization is used as a measure of domestic technological capabilities. Time-series-cross-section-growth regressions with development level interactions are used to test the stability of these variables' growth impact. The results show that real undervaluation is a growth driver across all development levels, once technological capabilities are accounted for; however, it is more important for developing and developed countries than for emerging markets. The results also suggest that developing countries grow faster when they are globally competitive in low-technology manufacturing and natural-resource-intensive industries. This research attempts to explain the lack of significance found in previous studies of the growth impact of real undervaluation in middle-income countries by accounting for an explicit role for domestic technological capabilities in the development process.
Keywords: O11; O14; O33; O47; 330; economic development; economic growth; domestic technological capabilities; real exchange rate undervaluation